2020
DOI: 10.1002/jso.26263
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 pandemic during Spain's state of emergency on the diagnosis of colorectal cancer

Abstract: Introduction: We evaluate the impact of COVID-epidemic in colorectal cancer (CRC) diagnosis during Spain's state of emergency. Methods: We compared newly diagnosed patients with patients diagnosed in the same period of 2019. Results: A new diagnosis of CRC decreased 48% with a higher rate of patients diagnosed in the emergency setting (12.1% vs. 3.6%; p = .048) and a lower rate diagnosed in the screening program (5.2% vs. 33.3%; p = .000). Conclusions: Fewer patients have been diagnosed with CRC, with a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 15 publications
(22 reference statements)
1
73
0
4
Order By: Relevance
“…While Belgium registered high numbers of deaths attributed to COVID-19 (with or without PCR confirmation), excess mortality during the first wave of the COVID-19 pandemic was comparable to average levels for Europe. 26 Despite the varied impact of the pandemic and the diversity of confinement measures to slow the spread of COVID-19 around the world, single-center and multicenter studies, from Italy, 5 , 15 Germany, 13 Austria, 12 Slovenia, 9 Poland, 2 Spain, 11 the UK, 1 and the USA, 3 , 4 , 6 , 14 as well as nationwide, population-level studies from the Netherlands 16 and Denmark, 17 all support a global decline in cancer diagnosis during the early stage of the pandemic. The scarcity of large, population-based studies on cancer diagnoses during the pandemic, to date, is presumably linked to delays in data collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Belgium registered high numbers of deaths attributed to COVID-19 (with or without PCR confirmation), excess mortality during the first wave of the COVID-19 pandemic was comparable to average levels for Europe. 26 Despite the varied impact of the pandemic and the diversity of confinement measures to slow the spread of COVID-19 around the world, single-center and multicenter studies, from Italy, 5 , 15 Germany, 13 Austria, 12 Slovenia, 9 Poland, 2 Spain, 11 the UK, 1 and the USA, 3 , 4 , 6 , 14 as well as nationwide, population-level studies from the Netherlands 16 and Denmark, 17 all support a global decline in cancer diagnosis during the early stage of the pandemic. The scarcity of large, population-based studies on cancer diagnoses during the pandemic, to date, is presumably linked to delays in data collection.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 Likewise, single-center and multicenter studies, and population-level studies focused on specific tumor types have reported declines in numbers of cancer diagnoses. 1 , 2 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 Evidence from large-scale studies quantifying these declines on a population level is limited. Two nationwide studies, from the Netherlands 16 and Denmark, 17 reported declines in the overall number of cancer diagnoses in March 2020 and March to May 2020, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Some examples are limitations of access to screening programmes, to medical care cancer-related visits (both in primary care and in hospitals), to cancer diagnostic tests, reduction in scheduled cancer surgeries due to limited access to postsurgical critical care units and occupation of hospital beds by patients with COVID-19, reduction of treatments that could pose a high risk to the patient in the circumstances of the pandemic, and modifications of therapeutic guidelines, among others. [18][19][20][21] In some countries, a reduction in cancer diagnostics and cancer encounters was observed. [22][23][24] This led to a reduction in new cancer diagnoses and a delay in cancer treatment.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The COVID-19 pandemic stopped or slowed many CRC screening programs. This interruption will have a great impact on the number of CRCs diagnosed and on the prognosis of newly diagnosed cases, which will, presumably, be diagnosed at an advanced stage (12)(13)(14). Resuming these programs is becoming a priority, but unfortunately, the new rules for preventing COVID-19 transmission have reduced the availability of colonoscopies in most health system (1,2,15).…”
Section: Discussionmentioning
confidence: 99%